Naturologia, religião e ciência: entremeares da construção de um campo - Leite, Ana Luisa Prosperi (2017)
Substantiated on counterculture claims and the amalgam between religious and scientific knowledges which are the foundation of New Era Movement, Naturology is instituted as an academic course on medical field by the end of the 1990’s in Brazil. A few years later initiates a path of academical production attempting to reach academical legitimacy. Its New Era foundations make Naturology to move in a pendular movement: although legitimation sought by the field and the activity regulation demand of its practices and researches a strict relation with official science, elements originated from religious traditions are inseparable of the therapeutics proposal offered by Naturology. Starting from this premise, the present study aims to reason how religious practices in Naturology communicate with scientific axiom on academic productions of the field. For such, were investigated the religious and secular world views on which the health concept used by Naturology were based on, differentiating what is in fact religious on the health practices used by the field. The academic productions considered as representative of the protagonists of the field were analyzed seeking to verify how these religious knowledge are correlated to Naturology, and under which terms were elaborated by its collocutor on the construction of an area own statement. It was observed that the religious aspects of Naturology are not mentioned on the area speech, which denies its practices as a continuation to esoteric knowledges. On the other way, as Naturology matures academically speaking, it is noticed the narrowing of the field with statements and research methodologies inherent to science and to official medicine, as well as the appropriation of scientific premises used to explain concepts protected by religious cosmologies. In this way, concludes that in its epistemological construction, Naturology is searching to be associated to a scientific speech that may explain the area assumptions, especially those controversial for been considered mystics or esoteric by common sense